2012
DOI: 10.1007/s11606-012-2229-8
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Performance Measures and 30-day Readmission Rates

Abstract: Hospitals with greater adherence to recommended care processes did not achieve meaningfully better 30-day hospital readmission rates compared to those with lower levels of performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 32 publications
(34 reference statements)
3
59
1
1
Order By: Relevance
“…In addition, our riskstandardization models differed from those used by CMS (14) by inclusion of markers of socioeconomic status and markers of severity of acute illness, as well as methods for identifying chronic comorbidities that could affect our observed associations. However, readmission rates in our study were similar to reports in Medicare data (21,23,32,33), and use of risk-adjustment models more similar to CMS did not substantially alter our findings.…”
Section: Limitationssupporting
confidence: 85%
“…In addition, our riskstandardization models differed from those used by CMS (14) by inclusion of markers of socioeconomic status and markers of severity of acute illness, as well as methods for identifying chronic comorbidities that could affect our observed associations. However, readmission rates in our study were similar to reports in Medicare data (21,23,32,33), and use of risk-adjustment models more similar to CMS did not substantially alter our findings.…”
Section: Limitationssupporting
confidence: 85%
“…35 Reducing the occurrence of readmissions has been difficult to achieve. 36 To our knowledge, this is one the first studies that suggests a beneficial association between HIE system usage and hospital readmissions in the USA. Until now, the studies that have been published about HIE interventions have not reported any association with reductions in readmissions, 15 and in fact, only a few studies have shown that hospitalizations, in general, may be reduced with HIE.…”
Section: Discussionmentioning
confidence: 85%
“…We also structured our model to account for the clustering of hospitals within states. 28,29 Finally, because we counted the number of consulting specialties, our results likely represent a lower bound, as multiple consultations may occur within a specialty (e.g., consulting both an interventional cardiologist and an electrophysiologist), but we had no way to accurately distinguish between cross-coverage within a new specialty and additional consultations. Further, we did not use evaluation and management codes for consultation, as these expired in 2009 and were used inconsistently in different regions and specialties, reflecting variation in billing practices rather than variation in consultation use.…”
Section: Discussionmentioning
confidence: 99%